Police without borders: the fading distinction between local and global - Roberson, Cliff; Das, Dilip K. (International Police Executive Symposium Co-Publications, 2010)
"Policing Without Borders: The Fading Distinction between Local and Global emphasizes the rising need for a cohesive international policing community. As crimes become more transnational in scope, the need for systematic communication between national police agencies becomes increasingly apparent. Various methods of collaboration need to address ways to institute global police communication. The chapters of this book focus on the theme of how local and global police practitioners and researchers can better collaborate on the mission of viewing policing with a global focus"--